Analisis Maqashid Syari’ah Jasser Auda Terhadap Izin Perkawinan Dan Perceraian Bagi Pegawai Negeri Sipil - Rahman, Fawait Syaiful (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2018)
Marriage under the provisions contained in the classical books of men who wish to have more than one wife, there is no requirement as regulated in the provisions of Government Regulation No. 45 of 1990 amendment to Government Regulation No. 10 of 1982 concerning Marriage and Divorce Permits Civil Servants, five sufficient conditions for the prospective wife, prospective husband, guardian, two witnesses, and sighat. While civil servants in the PP Article 4 Paragraph 1 men who want to have polygamy should seek permission from their superiors and Religious Courts. According to the researcher need to do re-analysis with appropriate methodology and precisely because the Government Regulation concerning state law order, in order to find whether Government Regulation Number 45 Year 1990 concerning Permit of Marriage and Divorce of Civil Servant have expediency or vice versa. For that the researcher chose Maqashid alShari'ah Jasser Auda as a knife of analysis in this study. This study aims to test empirically the variables that have been formulated in the formulation of the problem, namely reveal the history of birth PP. No. 45 Th. 1990 amendment of PP. No. 10 Th. 1983 on the marriage and divorce of civil servant, the application of the theory of Maqashid al-Shari'ah Jasser Auda to the PP. No. 45 Th. 1990, and analyzed the PP. No. 45 Th. 1990 amendment of PP. No. 10 Th. 1983 on marriage permit and divorce of civil servants with the theory of Maqashid al-Shari'ah Jasser Auda. Research Methods with Approach and Type of Research is a qualitative approach oriented to the statutory approach (Statute Aproach) with the type of research Library (library research). Methods of data collection using documentation, and data analysis using descriptive - inductive